Optimization Of Bar Linkage By Using Genetic Algorithms - Ramasamy, Mugilan (Universiti Sains Malaysia, 2005)
This thesis presents the method of using simple Genetic Algorithms (GAs) in optimizing the size of bar linkage with discrete design variables and continues design variables. Penalty-based transformation method is used in this thesis to change the constrained problems into unconstrained ones. It is well known that GAs is best suited for unconstrained optimization problems. Optimization process will consider, lightest weight of the bar by using GAs without exceeding the allowable stress determined. Two types of problems are chosen to optimize in this thesis. First problem is optimization of four bar linkage under static loading condition and second problem is optimization of four bar linkage under dynamic condition without loading. The result from GA for this problem is compared with some other methods which are presented by V.V Tropov and V.L Markine.It is observed that GA gives better solution compared to other published methods.